Land degradation and metropolitan expansion in a peri-urban environment. Issue 1 (1st January 2021) - Imbrenda, Vito; Quaranta, Giovanni; Salvia, Rosanna; Egidi, Gianluca; Salvati, Luca; Prokopovà, Marcela; Coluzzi, Rosa; Lanfredi, Maria
Abstract: The couple rapid urbanization and policy failure in controlling urban expansion was sometimes associated to soil and land degradation phenomena in both developing and developed countries. This work points to investigate the link between exurban development and soil/land degradation in the region of Athens (Greece) as a typical semiarid Mediterranean area experiencing a shift from a land-saving compact urban form to a dispersed, low-density urban expansion. The examined area is among the most populated areas in the Mediterranean basin showing an enormous population growth during the last 60 years. While low-density, dispersed urban settlements mainly developed over the decade (2000–2010) in the investigated area occupied mostly land classified at poor soil quality, the overall assessment of vegetation, climate and soil quality layers renders a complex picture in which exurban development consumed high-quality land that were classified as non-vulnerable to land degradation. On the contrary, compact urban settlements prevail in land with intermediate (or even high) soil quality but with inadequate climatic and vegetation conditions, which are classified as highly vulnerable to land degradation. Urban planning should integrate multi-dimensional indicators of soil, climate and vegetation quality to evaluate the environmental impact of exurban development.